Kajian faktor kejayaan dan pencapaian usahawan Muslim di Malaysia / Yazilmiwati @ Hasni Yaacob - Yazilmiwati @ Hasni, Yaacob (2016)
In most research of entrepreneurial success factors, the study is focused on success factors which have been put forward by western researchers. There are only a few empirical studies that look into the success factors from the perspective of Islam. Therefore, this research will combine entrepreneurial success factors from Western and Islamic perspective, by determining the relationship of the entrepreneurial success factors which comprise of entrepreneur’s personality, morale (akhlak), jihad business and the survival of entrepreneurs in the underlying business with the achievement of successful entrepreneurs in Malaysia This research adopts the mixed method, which is intended to produce a solid quantitative and qualitative research in order to fully understand the research phenomenon. Data was collected through questionnaires and interviews were conducted to successful entrepreneurs in Malaysia. This survey includes 206 entrepreneurs, of which 10 were interviewed. All of the entrepreneurs involved in the survey meet the criteria of the achievement of a successful entrepreneur as outlined in this research. Data collected via questionnaires were analyzed using a statistical ANOVA approach, T test, Spearman Rho, correlation and linear regression. The end of the result revealed that there is a positive and significant correlation between the success factors of entrepreneurs with successful entrepreneurs’ achievement in Malaysia. Data obtained via interviews, on the other hand, were analyzed to see the themes of relationship between the success factors and achievement of Muslim entrepreneurs. Results of this concluded that the themes of relationship between the factors of success and achievement of Muslim entrepreneurs exist as profiled in this study. As a result of using this mixed method, there is a continuity between the results of quantitative and qualitative methods towards the factors of success and achievement of Muslim entrepreneurs in Malaysia.